2012
DOI: 10.1152/ajpregu.00227.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity of lung vagal C fibers induced by acute intermittent hypoxia in rats: role of reactive oxygen species and TRPA1

Abstract: of lung vagal C fibers induced by acute intermittent hypoxia in rats: role of reactive oxygen species and TRPA1. Am J Physiol Regul Integr Comp Physiol 303: R1175-R1185, 2012. First published October 17, 2012 doi:10.1152/ajpregu.00227.2012.-Obstructive sleep apnea, manifested by intermittent hypoxia and excess production of reactive oxygen species (ROS) in airways, is associated with hyperreactive airway diseases, but the mechanism remains unclear. Sensitization of lung vagal C fibers (LVCFs) contributes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In these studies [14][16], these exaggerated responses could be prevented by pretreatment with antioxidants, indicating that there seemed to be an involvement of ROS in the sensitization of airway C-fibers and the development of airway hypersensitivity. However, questions remained as to whether the suppressive effects of the antioxidants in these studies resulted from a prevention of sensitization of the afferent fibers by the increased ROS or occurred because there was a removal of the basal function of ROS, which led to diminished afferent fiber sensitivity to these airway insults.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In these studies [14][16], these exaggerated responses could be prevented by pretreatment with antioxidants, indicating that there seemed to be an involvement of ROS in the sensitization of airway C-fibers and the development of airway hypersensitivity. However, questions remained as to whether the suppressive effects of the antioxidants in these studies resulted from a prevention of sensitization of the afferent fibers by the increased ROS or occurred because there was a removal of the basal function of ROS, which led to diminished afferent fiber sensitivity to these airway insults.…”
Section: Discussionmentioning
confidence: 88%
“…It has been previously shown that acute intermittent hypoxia [14] and laryngeal insult with acid and pepsin [15], [16] are able to potentiate the afferent and/or reflex responses of the airway C-fibers to stimulants in rats; the potentiating effect of the former and latter insults were found to be mediated through the TRPA1 and P2X receptors, respectively. In these studies [14][16], these exaggerated responses could be prevented by pretreatment with antioxidants, indicating that there seemed to be an involvement of ROS in the sensitization of airway C-fibers and the development of airway hypersensitivity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, TRPM8 (transient receptor potential M8) and TRPA1 (transient receptor potential A1) affect human physiology by initiating responses to volatile chemical agents or cold air via Ca 2+ -mediated activation of the peripheral nervous system, epithelia and underlying tissues [68]. They are modulated by specific biochemical species [9,10] or cell stress [11,12] and both TRP channels may be involved in pathological conditions such as asthma, chronic obstructive pulmonary disease and chronic cough [1316]. Hence they are emerging targets for pharmacological intervention [17].…”
Section: Introductionmentioning
confidence: 99%